3-D numerical analysis of train-induced flow inside four ventilated underground subway stations and connecting tunnels. Issue 193 (October 2019) - Izadi, Tahereh; Mehrabian, Mozaffar Ali; Abouali, Omid; Ahmadi, Goodarz
Abstract: The piston effect due to train movement in a subway system significantly affects the ventilation system in the stations and connecting tunnels. In this study the train movement in the subway tunnels and stations is simulated using a 3-D computational model and the transient airflow field around the train is studied. The unsteady RANS, and energy equations are solved for three dimensional compressible turbulent airflows using the dynamic mesh technique. The numerical model is validated by comparing the predicted results with the experimental data available in the literature. The computational domain consists of four stations and the connecting tunnels. The results show that the airflow rate in the main tunnel in which the train is moving can be quadrupled with respect to the stationary situation and the flow rate in the neighbor tunnel connecting to the next station can be tripled. The results also reveal that the airflow velocity in certain region of the platform can become too high and might give rise to the wind speed discomfort for waiting passengers. Finally, a simplified equivalent axisymmetric model is proposed and the results are compared with those obtained from the 3D model, good agreement is found especially in the tunnels. Highlights: Due to the piston effect, the airflow rate changes in the main and neighbor tunnels. The piston effect changes flow direction around fan openings; even in neighbor tunnels. For a higher train acceleration, a larger first pressure rise in tunnel is obtained. The airflow velocity in some regions of the platform gives rise to the wind discomfort. A simplified equivalent axisymmetric model can approximately represent a 3D model.